BS EN IEC 60966-4-2. Radio frequency and coaxial cable assemblies. Part 4-2. Detail specification for semi rigid cable assemblies (jumper), Frequency range up to 6000MHz, Type 50-9 semi-rigid coaxial cable, applicable to ISO/IEC 11801-1 (15th November 2019) - British Standards Institution,
No abstract available